Formation routes and structural details of the CaF1 layer on Si(111) from high-resolution noncontact atomic force microscopy data - Rahe, Philipp; Smith, Emily F.; Wollschläger, Joachim; Moriarty, Philip J. (American Physical Society, 2018)
We investigate the CaF1/Si(111) interface using a combination of high-resolution scanning tunnelling and noncontact atomic force microscopy operated at cryogenic temperature as well as x-ray photoelectron spectroscopy. Submonolayer CaF1 films grown at substrate temperatures between 550 and 600 ◦C on Si(111) surfaces reveal the existence of two island types that are distinguished by their edge topology, nucleation position, measured height, and inner defect structure. Our data suggest a growth model where the two island types are the result of two reaction pathways during CaF1 interface formation. A key difference between these two pathways is identified to arise from the excess species during the growth process, which can be either fluorine or silicon. Structural details as a result of this difference are identified by means of high-resolution noncontact atomic force microscopy and add insights into the growth mode of this heteroepitaxial insulator-on-semiconductor system.